Reactie op Devos. Managerpolitiek in de jaren tachtig was populair in de openbaarheid - Kroeze, Ronald; Keulen, Sjoerd (BMGN - Low Countries Historical Review, 2012)
Response to DevosIn response to Devos we argue that by reducing managerial politics to just another form of businesslike politics one diminishes twentieth century political history to an amorphous period of businesslike politics without changes. What distinguishes managerial politics from other forms of politics is not the businesslike behaviour of politicians, but their conscious, open and proud presentation of themselves as managers and their appraisal of management books as (ideological) sources of inspiration for policy making. To understand the rise of management in politics historians should pay more attention to public administration and management science. This makes clear that in the 1970s management itself changed fundamentally, which accounts for the popularisation of management in the 1980s. Finally, like all political style periods, managerial politics came to an end, symbolised in the Netherlands by the elections of 2002. Since then management has been used only in negative terms by politicians. This article is part of the forum 'Manager Politics'.